Nicorandil-Induced Hyperkalemia in a Uremic Patient - Lee, Hung-Hao (Hindawi Publishing Corporation, 2012)
Nicorandil is an antianginal agent with nitrate-like and ATP-sensitive potassium channel activator properties. After activation of potassium channels, potassium ions are expelled out of the cells, which lead to membrane hyperpolarization, closure of voltage-gated calcium channels, and finally vasodilation. We present a uremic case suffering from repeated junctional bradycardia, especially before hemodialysis. After detailed evaluation, nicorandil was suspected to be the cause of hyperkalemia which induced bradycardia. This case reminds us that physicians should be aware of this potential complication in patients receiving ATP-sensitive potassium channel activator.